A numerical study of stellar discs in galactic nuclei. Issue 4 (25th November 2022) - Panamarev, Taras; Kocsis, Bence
ABSTRACT: We explore the dynamics of stellar discs in the close vicinity of a supermassive black hole (SMBH) by means of direct N -body simulations. We show that an isolated nuclear stellar disc exhibits anisotropic mass segregation meaning that massive stars settle to lower orbital inclinations and more circular orbits than the light stars. However, in systems in which the stellar disc is embedded in a much more massive isotropic stellar cluster, anisotropic mass segregation tends to be suppressed. In both cases, an initially thin stellar disc becomes thicker, especially in the inner parts due to the fluctuating anisotropy in the spherical component. We find that vector resonant relaxation is quenched in the disc by nodal precession, but it is still the most efficient relaxation process around SMBHs of mass $10^6\, {\rm M}_{\odot }$ and above. Two-body relaxation may dominate for less massive SMBHs found in dwarf galaxies. Stellar discs embedded in massive isotropic stellar clusters ultimately tend to become isotropic on the local two-body relaxation time-scale. Our simulations show that the dynamics of young stars at the centre of the Milky Way is mostly driven by vector resonant relaxation leading to an anticorrelation between the scatter of orbital inclinations and distance from the SMBH. If the S -stars formed in a disc less than 10 Myr ago, they may coexist with a cusp of stellar mass black holes or an intermediate mass black hole with mass up to $1000\, {\rm M}_{\odot }$ to reproduce the observed scatter of angular momenta.